Farmer demand for climate services: Survey results from Ha Tinh province, Vietnam - Thoai Quang Trinh; Simelton, Elisabeth; Tam Thi Le (2018)
An info note published by the CGIAR Research Program on Climate Change, Agriculture, and Food Security (CCAFS) documented a study about the use of farmer-specific climate services. According to the study, climate services such as weather forecasts and agro-advisories contribute greatly in farming activities starting from planting to managing and harvesting seasons. Specifically, these services help farmers reduce or avoid yield loss and other weather-related damages. Realizing the benefits of using climate services, more farmers, specifically the younger ones, are now willing to pay for them.